Tuberculous lymphadenitis of the neck: Case series - Asuquo, Maurice Efana; Nwagbara, Victor I; Ebughe, Godwin; Agbor, Cyril; Akpan, Samuel; Ugbem, Theophyllus; Asuquo, Inyang M (International Journal of Medicine, 2013)
Tuberculous lymphadenitis is the most common form of extra pulmonary tuberculosis and cervical lymph nodes constitute the most common site of involvement. The proportion of extra pulmonary patients has been increasing for the last two decades. Presented are 3 consecutive female patients aged 32, 50, and 68 years that presented to a surgical unit of the University of Calabar Teaching Hospital, Calabar, Nigeria. Two patients presented with lesions located in the anterior triangle of the neck, while the third had bilateral lesions located in the posterior triangle of the neck. All were referrals without prior diagnosis of tuberculosis. Diagnosis was by cytology and histology. Notable associations were miliary tuberculosis and anaemia. Provision of appropriate and effective prevention modalities, diagnostic facilities, and effective surveillance from the primary to the tertiary health facilities for early detection and treatment of the disease is advocated.